PENENTUAN DISTRIBUSI STATIONER JARINGAN SIKLIK JACKSON DENGAN METODE REDUKSI RANK - Novita Dwi Maharani Sabban (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to test the model a Cyclic Networks Jackson as a form of Markov and determine vectors opportunities stationary queuing models with reduction method Rank. This study uses the method of literature; which examines several theories relating to the determination of stationary distribution network with cyclical Jackson Rank Reduction method. The least squares method is used for the linear regression model parameter estimation, besides using also methods Bootstrap resampling method Nonparameter as data errors randomly and independently with replacement. The results showed that (1) Network cyclic Jackson with 2 station and 3 station can be modeled in the form of Markov. (2) Distribution network stationary cyclic two stations depends on the value of the transition from station 1 to station 2 and the value of the transition from station 2 to station 1, (3) rank reduction method can be used to determine the stationary distribution of the network cyclic Jackson. This method reduces the rank matrix Q builders are generally greater than one, to then generate a matrix with a rank equal to one.